HOUSEHOLD HARMONY IN SALAFI FAMILIES: PERSPECTIVES OF USTADZ WIVES IN JEMBER - Hermawan, Almaira Raila; Syarafuddin, Muhsan (Program Studi Hukum Keluarga Fakultas Syariah UIN Datokarama Palu, 2025)
Islam provides clear household guidelines to obtain harmony (sakinah). On the other hand, many contemporary Muslim families face dynamic challenges, particularly debates surrounding the role of wives. While previous studies have examined family harmony from various perspectives, empirical research on the lived experiences of Salafi wives remains limited. This study addresses that gap by exploring how the wives of Salafi ustadz in Jember understand and practice household harmony within the framework of Islamic teachings. Using a qualitative case study approach with purposive sampling, ten respondents were interviewed and observed. The findings reveal five key perspectives on achieving harmony: (1) choosing a religious husband; (2) possessing and applying Islamic knowledge; (3) maintaining good communication; (4) orienting toward afterlife happiness; and (5) prioritizing faith over emotional dependency. At the same time, they identified four major challenges: (1) balancing domestic and gendered responsibilities; (2) negotiating religious identity in a conflicting social environment; (3) addressing emotional and communication needs; and (4) managing economic difficulties. This study contributes to Islamic family law and gender discourse by demonstrating how Salafi wives integrate Qur’an- and Sunnah-based principles into family life while navigating modern household dynamics.